3(y+6)=2y-2

Simple and best practice solution for 3(y+6)=2y-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(y+6)=2y-2 equation:


Simplifying
3(y + 6) = 2y + -2

Reorder the terms:
3(6 + y) = 2y + -2
(6 * 3 + y * 3) = 2y + -2
(18 + 3y) = 2y + -2

Reorder the terms:
18 + 3y = -2 + 2y

Solving
18 + 3y = -2 + 2y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-2y' to each side of the equation.
18 + 3y + -2y = -2 + 2y + -2y

Combine like terms: 3y + -2y = 1y
18 + 1y = -2 + 2y + -2y

Combine like terms: 2y + -2y = 0
18 + 1y = -2 + 0
18 + 1y = -2

Add '-18' to each side of the equation.
18 + -18 + 1y = -2 + -18

Combine like terms: 18 + -18 = 0
0 + 1y = -2 + -18
1y = -2 + -18

Combine like terms: -2 + -18 = -20
1y = -20

Divide each side by '1'.
y = -20

Simplifying
y = -20

See similar equations:

| 6=0x | | x+(x+1)=(x+2)-(x-1) | | 3-t/6=7 | | C=81000+18x | | 11a+9a=4a+30 | | 5w^2-2w+3=0 | | x^2+18x+90x=0 | | (7t-3)-(3t+1)=-3(1-3t) | | -2-42=x | | 5.60+.25x=19.85 | | 45x-11=250 | | 2x^2+16x+5= | | x*x+12x+32=0 | | 5(3p-5)+4p=5p-6(p+4) | | 14*30b=-196 | | 176-0.8a=122+a | | 5x+2(3x-4)=80 | | 8x+4y=22 | | -17=v | | 3x+50i=18-5yi | | 45-11x=250 | | y-94=5(x-9) | | -4p-13p-p=-150 | | 4y-14=30 | | 14*30+b=-192 | | y-2=5(x+3)fory | | y-9=5(x+8) | | 175+15d=250 | | 61n=187 | | 81-16t^2= | | 33=9-y | | 4w+3=2(w+1)+2w |

Equations solver categories